Nevoid acanthosis nigricans: a rare case with late onset - Mrinal Gupta; Vikram K Mahajan; Suman Singh (Our Dermatology Online, 2015)
Nevoid acanthosis nigricans is a rare variant usually presents as a localized hyperpigmented velvety plaque at birth or before puberty. However, unlike other variants, it is neither localized to the neck or flexures nor associated with metabolic disturbances, syndromes, drug toxicity, endocrinopathy or malignancy. Only a few cases of nevoid acanthosis nigricans have been reported in the literature. This 17-year-old male presented with a gradually progressive hyperpigmented, velvety plaque of nevoid acanthosis nigricans over the midline of the abdomen having a late onset.